Human neutrophils employ chlorine gas as an oxidant during phagocytosis. - Hazen, S L (1996)
Reactive oxidants generated by phagocytes are of central importance in host defenses, tumor surveillance, and inflammation. One important pathway involves the generation of potent halogenating agents by the myeloperoxidase-hydrogen peroxide-chloride system. The chlorinating intermediate in these reactions is generally believed to be HOCl or its conjugate base, ClO-. However, HOCl is also in equilibrium with Cl2, raising the possibility that Cl2 executes oxidation/ halogenation reactions that have previously been attributed to HOCl/ClO-. In this study gas chromatography-mass spectrometric analysis of head space gas revealed that the complete myeloperoxidase-hydrogen peroxide-chloride system generated Cl2. In vitro studies demonstrated that chlorination of the aromatic ring of free L-tyrosine was mediated by Cl2 and not by HOCl/ClO-. Thus, 3-chlorotyrosine serves as a specific marker for Cl2-dependent oxidation of free L-tyrosine. Phagocytosis of L-tyrosine encapsulated in immunoglobulin- and complement-coated sheep red blood cells resulted in the generation of 3-chlorotyrosine. Moreover, activation of human neutrophils adherent to a L-tyrosine coated glass surface also stimulated 3-chlorotyrosine formation. Thus, in two independent models of phagocytosis human neutrophils convert L-tyrosine to 3-chlorotyrosine, indicating that a Cl2-like oxidant is generated in the phagolysosome. In both models, synthesis of 3-chlorotyrosine was inhibited by heme poisons and the peroxide scavenger catalase, implicating the myeloperoxidase-hydrogen peroxide system in the reaction. Collectively, these results demonstrate that myeloperoxidase generates Cl2 and that human neutrophils use an oxidant with characteristics identical to those of Cl2 during phagocytosis. Moreover, our observations suggest that phagocytes exploit the chlorinating properties of Cl2 to execute oxidative and cytotoxic reactions at sites of inflammation and vascular disease.